Case Report: Characterization of a RAC2 R68W homozygous activating mutation causing combined immune deficiency - Desjardins, Aléhandra; Marois, Louis; Donkó, Ágnes; Cros, Guilhem; Bédard, Marc-Antoine; Paul, Marie-Lorna; Hsu, Amy P.; Darbinian, Emma; Gosse, Géraldine; Leto, Thomas L.; Chapdelaine, Hugo; Massé, Chantal; et al. (Frontiers in Immunology, 2026)
RAC2-related immunodeficiency is a rare inborn error of immunity with a broad clinical spectrum ranging from neonatal severe combined immunodeficiency to atypical combined immunodeficiency diagnosed later in life. We describe two unrelated French-Canadian patients carrying a rare, homozygous RAC2 variant (c.202C>T; p.R68W), both presenting with combined immunodeficiency. The first patient developed recurrent bacterial respiratory infections and early bronchiectasis that initially responded to immunoglobulin replacement therapy. She subsequently experienced severe, treatment-refractory cutaneous viral infections. In adulthood, she developed gynecologic and anal neoplasms associated with chronic viral disease, requiring long-term multidisciplinary management. The second patient presented in early childhood with recurrent respiratory infections, marked lymphoproliferation, and generalized lymphadenopathy. He then developed kidney dysfunction due to light-chain deposition disease. Management included immunoglobulin therapy, and ultimately hematopoietic cell transplantation (HCT), after which he achieved sustained clinical improvement. Genetic testing identified the same homozygous p.R68W substitution in both patients. Despite significantly reduced RAC2 protein expression, patient-derived cells exhibited increased effector signaling in the homozygous state, producing a phenotype that phenocopies dominant gain-of-function RAC2 variants. Functional hyperactivation was not observed in heterozygous cells, supporting a dosage-dependent mechanism. These cases expand the clinical and functional spectrum of RAC2 deficiency and have immediate implications for clinical care. Persistent viral disease with oncogenic complications, bronchiectasis, lymphoproliferation, or progressive organ involvement should prompt consideration of RAC2 testing even beyond infancy. From a diagnostic standpoint, reliance on expression alone may be misleading; incorporating targeted signaling assays is essential for accurate variant interpretation. Therapeutically, HCT can be effective in progressive disease with organ damage, while others may require long-term medical management of chronic viral complications. Recognizing this rare, homozygous p.R68W variant and its functional consequences supports a precision-diagnosis approach to RAC2-related immunodeficiency and refines surveillance and treatment strategies for affected patients.